2012
DOI: 10.3989/gya.106611
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of industrially produced reduced and low fat Turkish white cheese as influenced by the homogenization of cream

Abstract: 267exhibited a more extended matrix with a few small fat globules compared to the defatted micrographs. Homogenization of cream produces small fat globules and unclustured fat globules were found in the resulting whey. These results are important for dairy processors for using cream homogenization as a processing tool at the industrial level. KEY-WORDS: Fat reduction -Homogenized cream -Microstructure -White cheese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
(39 reference statements)
0
8
0
1
Order By: Relevance
“…Li‐Chan et al , by contrast, provided a more general overview of ways in which vibrational spectroscopy has been applied to food analysis in the literature . Cheese microstructure, however, has largely been monitored in the literature using scanning electron microscopy (SEM), which has been used on various cheese types including: cream cheese, Edam‐like cheese and Turkish white cheeses . Such studies have found that the technique is useful for observing microstructural changes in fat globule size and the protein matrix after changing the pH, freeze‐fracturing and homogenization …”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Li‐Chan et al , by contrast, provided a more general overview of ways in which vibrational spectroscopy has been applied to food analysis in the literature . Cheese microstructure, however, has largely been monitored in the literature using scanning electron microscopy (SEM), which has been used on various cheese types including: cream cheese, Edam‐like cheese and Turkish white cheeses . Such studies have found that the technique is useful for observing microstructural changes in fat globule size and the protein matrix after changing the pH, freeze‐fracturing and homogenization …”
Section: Introductionmentioning
confidence: 93%
“…[25] Cheese microstructure, however, has largely been monitored in the literature using scanning electron microscopy (SEM), which has been used on various cheese types including: cream cheese, Edam-like cheese and Turkish white cheeses. [26][27][28] Such studies have found that the technique is useful for observing microstructural changes in fat globule size and the protein matrix after changing the pH, [26] freeze-fracturing [27] and homogenization. [28] This research aimed to determine whether the distribution of various components within processed cheese can be imaged using Raman microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical example of this is homogenization and micro-fluidisation. These processes reduce the milk fat particle size (Karaman et al, 2012;Madadlou et al, 2007) and decrease curd firmness and syneresis (Lemay et al, 1994). Homogenization of milk can not only increase the yield of cheese but also reduce the amount of fat loss in to whey (Kelly et al, 2008;Zamora et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the studies so far (Deegan et al, 2013;Karaman and Akalın, 2013;Logan et al, 2015;O'Mahony et al, 2005) have reported on the effect of size of MFGs and homogenization on reduced fat and full fat cheeses only. Other studies (Karaman et al, 2012;Nair et al, 2000;Tahereh et al, 2017;Van Hekken et al, 2007) suggested homogenization as one of the modifying techniques to improve the textural and other characteristics of low fat cheeses, but did not study the effect of emulsion size. Incorporation of milk fat emulsions in micron to nanosize range as a texture modifier in low-fat Cheddar cheese has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%